The Effect of Independence, Objectiveness and Competence on The Quality of Audit Results - Dzakwan, Sulthan Dhaifullah; Yuliati, Anik (Jurnal Akuntansi dan Perpajakan, 2024)
This research aims to empirically test and analyze the effect of independence, objectivity and competence on the quality of audit results at the Surabaya City Public Accounting Firm. The population in this study were auditors working at 52 Public Accounting Firms (KAP) in the Surabaya City area. The sampling technique used in this research convenience sampling and obtained as many as 9 Public Accounting Firms (KAP) containing 72 respondents (auditors) in the Surabaya City area through distributing questionnaires. The data analysis method used is multiple linear regression analysis refers to a statistical technique that uses two or more independent variables to predict the outcome of a dependent variable. The technique enables analysts to determine the variation of the model and the relative contribution of each independent variable in the total variance. The results indicate that only competence had an effect in the quality of audit results while independence and objectivity had no effect in the quality of audit results. This finding contributes to the need to consider competence is based on the auditor’s experience, education and knowledge so that it can produce quality audits.